2003
DOI: 10.1161/01.cir.0000087391.49121.ce
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Surgery Can Now Routinely Be Performed Endoscopically

Abstract: Background— There is an increasing interest in minimally invasive cardiac surgery. Methods and Results— Since February 1, 1997 till April 1, 2002, 306 patients underwent endoscopic mitral valve surgery (226 repair, MVP; 80 replacement, MVR). Predominant valve pathology was degenerative in MVP (83.6%) and rheumatic in MVR (65%). Mean age was 61.5±12.9 years. Median preoperative functional class (MVP+MVR) and mitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
122
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 25 publications
(19 reference statements)
3
122
0
Order By: Relevance
“…A complication of aortic endoclamping much reported in the literature [40,45,46] also occurred in our series. A dissection of the atrioventricular groove and rupture of the left ventricle were observed in a patient with mitral valve surgery in advance on which we used the method.…”
Section: Discussionsupporting
confidence: 81%
“…A complication of aortic endoclamping much reported in the literature [40,45,46] also occurred in our series. A dissection of the atrioventricular groove and rupture of the left ventricle were observed in a patient with mitral valve surgery in advance on which we used the method.…”
Section: Discussionsupporting
confidence: 81%
“…Data from the Society of Thoracic Surgery (STS) show that less than 20% of valve surgeries are performed by minimally invasive incisions, and there are few centers that make these surgeries more routine [1,2,9]. In our country, that number should be even lower, given the small number of publications on minimally invasive valve surgery, and with relatively small case series [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the technique, our dissection of the intercostal spaces is minimal and corresponding for the size of the incision in the skin, and the removal of the intercostal space is limited, avoiding trauma to the ribs and thereby decreasing postoperative pain. Some centers advocate the use of video or robotic systems for performing these surgeries [4,9,11]. In Brazil, Poffo et al [11] reported their experience of minimally invasive surgeries with the aid of video, including being performed a pioneering procedure by periareolar access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimally invasive access advanced from partial sternotomy to anterolateral minithoracotomy and from direct vision via endoscopic guidance to totally endoscopic procedures (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%